A 3D injectable and enzymatic responsive hydrogel-bioceramic system for bone tissue engineering - Chun, Yong Yao (2017)
Autologous bone graft is the current gold standard to treat bone defects caused by trauma, tumour and pathological fracture. The superior healing properties of the autologous bone graft are due to the presence of periosteum that provides angiogenic and osteogenic properties for bone healing. However, the extraction of autologous bone graft will cause donor morbidity on patient. Inspired by the periosteum, this thesis aimed to develop a novel periosteum-inspired system as an injectable bone scaffold. First, phenol-conjugated gelatin hydrogel with tunable properties using different amounts of horseradish peroxidase and hydrogen peroxide was developed as the potential injectable bone scaffold. Next, phenol-conjugated carboxymethyl cellulose was incorporated into this hydrogel to introduce post-fabrication tunability to tailor the degradation and release behavior using cellulase, which could induce drug release and enhance cell proliferation. Finally, fish scale-derived calcium phosphate was incorporated to develop the hydrogel-bioceramic composite to improve its mechanical and bioactive properties.